Construction and Validation of an Immune-Based Prognostic Model for Pancreatic Adenocarcinoma Based on Public Databases - Mao, Miaobin; Ling, Hongjian; Lin, Yuping; Chen, Yanling; Xu, Benhua; Zheng, Rong (Frontiers in Genetics, 2021)
Background: Pancreatic adenocarcinoma (PAAD) is a highly lethal and aggressive tumor with poor prognoses. The predictive capability of immune-related genes (IRGs) in PAAD has yet to be explored. We aimed to explore prognostic-related immune genes and develop a prediction model for indicating prognosis in pancreatic adenocarcinoma (PAAD). Methods: The mRNA expression profiles acquired from public databases were comprehensively integrated and differentially expressed genes (DEGs) were identified. Univariate analysis was utilized to identify IRGs that related to overall survival. Whereafter, a multigene signature in the TCGA cohort was established based on the Lasso Cox regression analysis. Moreover, a TFs regulatory network was constructed to reveal potential molecular processes in PAAD. PAAD datasets downloaded from the GEO database were applied for the validations. Finally, correlation analysis between the prognostic model and immunocyte infiltration was investigated. Results: Totally, 446 DEIRGs were screened in PAAD tissues and normal tissues, of which 43 immune-related genes were significantly related to the overall survival of PAAD patients. An immune-based prognostic model was developed, which contained eight IRGs. Univariate and multivariate Cox regression revealed that the risk score model was an independent prognostic indicator in PAAD (HR> 1, P< 0.001). Besides, the sensitivity of the model was evaluated by the receiver operating characteristic (ROC) curve analysis. Finally, immunocyte infiltration analysis revealed that the eight-gene signature possibly played a pivotal role in the status of the PAAD immune microenvironment. Conclusions: A novel prognostic model based on immune genes may serve to characterize the immune microenvironment and provide a basis for pancreatic adenocarcinoma immunotherapy.